Management of Post Traumatic Posterior Urethral Sticture - Khan, Mazhar; Ahmad, Mushtaq (Journal of Postgraduate Medical Institute, 2011)
The management of post traumatic posterior urethral sticture is one of the most difficult surgical problem faced by urologist. It is an uncommon injury at an inaccessible location. We present our data of 22 patients. Who had one stage perineal urethroplasty and were followed for more than one year. We compare the results of initial suprapubic catheterization at the time of injury and delayed urethroplasty, with patient, who had initial realignment procedure with railroading and presented to us with recurrent stricture formation. The result of primary catheterization and delayed urethroplasty is very satisfactory and is asscoaited with fewer side effects compared to primary urethral realignment procedure. all described is the surgical technique used in the repair.